The Big Switch in Latin America : Restoring Growth through Trade - de la Torre, Augusto (Washington, DC: World Bank, 2016)
This report, produced by the Office of the Chief Economist for Latin America and the Caribbean (LAC) of the World Bank, examines LAC’s challenges as the global economy settles to an equilibrium with lower growth and lower commodity prices. Chapter 1 gives an overview of the world economy and how it affects LAC’s short and medium-term prospects. It argues that LAC suffered an external shock that shaped growth in recent years, and that the current global context is likely here to stay. Many LAC countries experienced significant depreciations which in principle should help adjust to the new equilibrium. The extent to which these depreciations facilitate a soft landing, however, depends on a number of factors. Chapter 2 explores the response of LAC’s trade to the recent depreciations and the role it could play in facilitating a recovery. It examines if there are early signs of an export recovery and whether the region’s increased dependence on commodity exports could hinder LAC’s recovery.